Snapdragons: The Tortoise and the Baboon - Howell, Gill; Woody (Oxford University Press UK, 2004)
Baboon asks Tortoise to dinner, but when Tortoise arrives, Baboon has eaten all the food! Tortoise is very angry so he asks Baboon to dinner, but makes him wash his hands first. Baboon runs to the river, but because he walks on all fours, his hands get dirty again. Tortoise keeps sending Baboon back to wash, and eats all the food himself